The Relationship Between Education and Intellectual Assets Value in the Innovation Performance of Some Eu Countries - Bene, Andrea; Csernák, József (Acta Carolus Robertus, 2024)
Today, intellectual creation and innovation are closely intertwined. Intellectual property rights are key to stimulating innovation, protecting investment and promoting technological progress. At the same time, it is important to strike a balance between encouraging innovation and the free flow of knowledge. The protection of intellectual property rights allows the free flow of knowledge between educational institutions and companies. The protection of new knowledge and technologies generated through cooperation is in the interest of all parties concerned. The study looks at the indicators of the EU Innovation Scoreboard on the level of education and intellectual property development and highlights the key role of education.